The Philosophy of the Matrilineal Kinship System as A Cultural Heritage of Minangkabau - Sri Agustina; Lisna Sandora; Yunika Lubis; Nabila Nabila; Kayyisa Hanifa (Yupa: Historical Studies Journal, 2026)
This study examines the philosophy underlying the Minangkabau matrilineal kinship system as a cultural heritage rich in meaning and social values. Using a qualitative descriptive approach and library research, the study finds that this system is not merely a social structure but also reflects gender balance, collective family responsibility, and a close relationship between custom and religion through the principle of adat basandi syarak, syarak basandi Kitabullah. Amid globalization and modernization, this philosophy remains relevant for strengthening cultural identity and shaping social character. The study therefore argues that understanding and preserving the philosophical foundations of the Minangkabau matrilineal kinship system is essential for sustaining the noble values of Indonesia’s cultural heritage.